PERBANDINGAN RASIO BOD/COD PADA AREA TAMBAK DI HULU DAN HILIR TERHADAP BIODEGRADABILITAS BAHAN ORGANIK - Tamyiz, Muchammad (2477 - 6165, 2015)
Pond is one place that is used as a place to cultivate fish, shrimp, and other aquatic animals that can live in brackish water. Changes in water quality upstream and downstream of the pond due to pollutants may affect the ecological balance of waters. Pollutants can be determined by two simple parameters, the biochemical oxygen demand (BOD) and chemical oxygen demand (COD). While the ability to break down pollutants (biodegradability) can be determined using the ratio of BOD/COD. BOD analysis using the Winkler titration method, whereas the COD analysis using titrimetric method. The value of BOD, COD, and the ratio of BOD/COD in the upstream area is 28.00 mg/L, 60.00 mg/L, and 0,467 respectively. While the value of BOD, COD, and the ratio of BOD/COD in the downstream area is 20.00 mg/L, 43.00 mg/L, and 0.465 respectively. Ratio BOD/COD obtained show that the organic pollutants in the pond is biodegradable.